Voleibol feminino na adolescência e os testes de impulsão vertical e horizontal - Moraes, Franco Fachin (My University, 2020)
We already know that the Woman´s Volleyball is a strong sport here in Brazil, having already devoted two-times Olympic Champion in 2008 and 2012. This completion of course work, is refent to the Jump Horizontal and vertical tests on the volleyball and the improvement perception, having as guiding question ?the results of the Jump Horizontal and vertical tests match with the maintenance perception or improvement of this action by the eight athlete of category under-13 and under-17 of volleyball in the club Associação dos Motoristas São-Marquenses (AMSM), in São Marcos/RS. The main objective in these study is analyse the relation of tests results with the improvement perception by this action by athlete of category under-13 and under-17 of volleyball in the club Associação dos Motoristas São-Marquenses (AMSM), in São Marcos/RS. The methodology used for this will be quantitative and qualitative with transversal character, experimental imprint, experimental characterization, using the inductive approach method.through data analysis it was detected thatof the eigth athletes, (50%) improve their vertical jump, (37%), improve their horizontal jump, besides, (37%), have a good perception with respect of the vertical jump test and (50%), have a good perception of the horizontal jump test. We can conclude that is necessary a phisycal improvement, besides a training adaptation, taking into account that the COVID-19 pandemic period when athletes were not regularly training the fundamentals of the sport [resumo fornecido pelo autor].
O voleibol feminino é um esporte muito forte aqui no Brasil, tendo já se consagrado Bicampeão olímpico nos anos de 2008 e 2012, o que motiva jovens atletas a buscar melhorar seu desempenho, e quem sabe uma futura ascensão na modalidade. Os testes físicos podem representar alguns índices de performance, e por conta disso o presente estudo se refere aos testes de impulsão vertical e horizontal no voleibol, e a autopercepção de melhora. O principal objetivo dessa pesquisa foi analisar a relação dos resultados dos testes de impulsão vertical e horizontal, com a percepção de manutenção ou melhora desta ação, por oito atletas de categoria sub-13 e sub-17 de voleibol no clube Associação dos Motoristas São-Marquenses (AMSM), da cidade de São Marcos/RS. A metodologia utilizada para a realização do mesmo foi qualitativa e quantitativa de caráter transversal. Através da análise de dados, foi constatado que das oito participantes, (50%) melhoraram sua impulsão vertical, (37%), melhoraram sua impulsão horizontal, além de (37%), apresentarem uma boa percepção com relação ao teste de impulsão vertical e (50%), apresentaram uma boa percepção do teste de impulsão horizontal. Podemos concluir que é necessária uma melhora física das mesmas, além de uma adaptação do treinamento, levando em conta o período de pandemia do COVID-19 onde as atletas não estavam treinando regularmente os fundamentos da modalidade [resumo fornecido pelo autor].
Keywords: Voleibol; Adolescência; Percepção